2014
DOI: 10.5468/ogs.2014.57.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of pelvic arterial embolization for postpartum hemorrhage: A retrospective review of 117 cases

Abstract: ObjectiveThe aim of this study was to evaluate indications, efficacy, and complications associated with pelvic arterial embolization (PAE) for postpartum hemorrhage (PPH).MethodsWe retrospectively reviewed the medical records of 117 consecutive patients who underwent PAE for PPH between January 2006 and June 2013.ResultsIn our single-center study, 117 women underwent PAE to control PPH refractory to conservative management including uterine massage, use of uterotonic agents, surgical repair of genital tract la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
50
2
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 26 publications
8
50
2
3
Order By: Relevance
“…Early reports with limited number of women have shown the potential of this technique that was later confirmed by larger studies [12][13][14][15][16][17][18][19]. Uterine atony accounts for the majority of causes of PPH and is the most common indication for TAE [20].…”
Section: Introductionmentioning
confidence: 99%
“…Early reports with limited number of women have shown the potential of this technique that was later confirmed by larger studies [12][13][14][15][16][17][18][19]. Uterine atony accounts for the majority of causes of PPH and is the most common indication for TAE [20].…”
Section: Introductionmentioning
confidence: 99%
“…When there is need of subsequent deliveries, the tendency is to choose a conservative surgical approach. This include uterine arteries ligation with or without ovarian arteries ligation 9 , B-Lynch suturing technique 8,9 , hypogastric arteries ligation (HAL) [10][11][12] and sometimes hypogastric arteries embolization [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…These earlier studies were also limited by the larger number of predictive factors and the lack of multivariate analysis. (9,20) Cheong et al have recently suggested that the observed correlation between PAE failure and increased blood transfusion may be a result of longer procedure times for patients with clinical failure, rather than increased blood transfusion being a causative predictor of embolisation failure by itself. (20) In our study, which was performed in a regional acute general hospital setting, urgent PAE showed a success rate of over 70%, with no maternal deaths or complications.…”
Section: Discussionmentioning
confidence: 99%
“…(9,20) Cheong et al have recently suggested that the observed correlation between PAE failure and increased blood transfusion may be a result of longer procedure times for patients with clinical failure, rather than increased blood transfusion being a causative predictor of embolisation failure by itself. (20) In our study, which was performed in a regional acute general hospital setting, urgent PAE showed a success rate of over 70%, with no maternal deaths or complications. Follow-up of our post-PAE patients showed that all clinically successful patients had subsequent return of menstruation, except for the patient who had pre-embolisation hysterectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation